Porokeratoma: A different entity or a variant of verrucous (Hyperkeratotic) porokeratosis? - Ana Batalla; Elena Rosón; Carlos De la Torre (Wolters Kluwer Medknow Publications, 2013)
Porokeratoma (acanthoma with features of porokeratosis) is a recently described entity with a distinct pattern of cornoid lamellation and clinically different from typical porokeratosis. We present a case of multiple porokeratomas on the buttock of a 78-year-old man with paraplegia secondary to poliomyelitis and ankylosing spondylarthritis. We briefly review the characteristics and controversies of this new entity.